Effect of budgetary participation in managerial performance with environmental uncertainty, leadership style, and budgetary adequacy as a moderating variable - Tokilov, Damaris Ussy; Suputra, I Dewa Gede Dharma; Rasmini, Ni Ketut (International research journal of management, IT and social sciences, 2019)
The purpose of this study was to examine the effect of budgetary participation on managerial performance with environmental uncertainty, leadership style, and budget adequacy as a moderating variable. This research uses contingency theory and Participative Decision-Making theory. The sampling technique used was purposive sampling, so the number of samples was 22 companies. Data analysis techniques using the Moderated Regression Analysis analysis technique. The results of this study indicate that the first hypothesis which states that budgetary participation influences managerial performance shows that a significant level of 0.002 is smaller than ? = 0.05, indicating H1 is accepted, which means that budgetary participation has a positive effect on managerial performance. The second hypothesis shows that a significant level of 0.037 less than ? = 0.05 signifies H2 being accepted, which means that environmental uncertainty reinforces the influence of budgetary participation on managerial performance. The third hypothesis shows that the significance level of 0.854 is greater than ? = 0.05, which means that the leadership style weakens the influence of budgetary participation on managerial performance. The fourth hypothesis shows that the significance level of 0.863 is greater than ? = 0.05, which means that the budgetary adequacy weakens the influence of budgetary participation on managerial performance.